2018
DOI: 10.1021/acsaem.8b00849
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Defects in WO3 Thin Films and Their Impact on Photoelectrochemical Water Splitting

Abstract: We evaluate the impact of defects in WO3 thin films on the photoelectrochemical (PEC) properties during water splitting. We study physical defects, such as micro holes or cracks, by two different deposition techniques: sputtering and atomic layer deposition (ALD). Chemical defects, such as oxygen vacancies, are tailored by different annealing atmospheres, i.e. air, N2, and O2. The results show that the physical defects inside the film increase the resistance for the charge transfer and also result in a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 64 publications
(133 reference statements)
1
41
0
Order By: Relevance
“…In order to decouple the contribution of the n-Si from WO3, we carried out PEC measurements with monochromatic light illumination. The idea is that due to the different bandgaps of n-Si (~ 1.1 eV [29] ) and WO3 (~3.0 eV from our previous work [36] ) one or the other materials can be excited selectively by a light source. A UV lamp with λ = 365 nm and an IR laser with λ = 980 nm were chosen to excite the WO3 and the n-Si, respectively.…”
Section: Pec Measurements Under Monochromatic Lightmentioning
confidence: 99%
“…In order to decouple the contribution of the n-Si from WO3, we carried out PEC measurements with monochromatic light illumination. The idea is that due to the different bandgaps of n-Si (~ 1.1 eV [29] ) and WO3 (~3.0 eV from our previous work [36] ) one or the other materials can be excited selectively by a light source. A UV lamp with λ = 365 nm and an IR laser with λ = 980 nm were chosen to excite the WO3 and the n-Si, respectively.…”
Section: Pec Measurements Under Monochromatic Lightmentioning
confidence: 99%
“…However, rather than act as recombination centers, oxygen vacancies appear to enhance catalytic activity in many metal oxide photocatalysts, including tungsten, indium, titanium, molybdenum, and zinc oxide. [3][4][5][6][7][8][9][10][11][16][17][18][19][20] Several studies have reported higher catalytic activity in these materials as the oxygen vacancy concentration is increased through thermal or chemical treatments, although various mechanisms have been proposed to explain this observation. 3-8, 10-11, 16 Density-functional-theory (DFT) calculations suggest that oxygen vacancies act both as preferential adsorption sites for reactant molecules and create new states within the electronic band gap of the semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, BiVO 4 exhibits a limited photocatalytic activity because of its poor charge transfer properties and slow water oxidation kinetics. [8,9] Various approaches to improve the water splitting efficiency of BiVO 4 have been tested, including morphology control, [10] doping, [11,12] construction of composite structures, [13] improved charge separation, [14] and combination with oxygen evolution catalysts. [9,15,16] Due to the fact that the oxygen evolution reaction is the rate-limiting step in solar-driven water splitting [17] the most promising way to enhance the properties of such devices is seen in the deposition of oxygen evolution catalysts (OECs) on the surface of the photoanode material.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, semiconducting oxides able to efficiently absorb visible light and resist to photo‐corrosion in aqueous solutions are the materials of choice for the fabrication of solar light‐driven photoelectrochemical water splitting devices . However, well‐known single‐metal‐oxide semiconductors, such as TiO 2 , WO 3 , Fe 2 O 3 , and ZnO present disadvantages, like low light absorption coefficients (WO 3 ), limiting hole transport (Fe 2 O 3 ) and absorption of light mostly in the UV range (TiO 2 , ZnO), and therefore do not display the required performance for application in solar to chemical energy conversion . BiVO 4 has emerged as a promising photoanode material mostly due to its small bandgap of 2.4 eV being located within the visible light range and the positions of the conduction and valance band edges, matching the potential for water reduction while being above the potential of water oxidation, respectively.…”
Section: Introductionmentioning
confidence: 99%